A Mulher encarcerada: estigma e justiça - Nogueira Porto, Dora; Raichtaler do Valle, Ida (Pontifícia Universidade Católica de São Paulo, 2019)
The social conflicts generated in the issue of the inequality of the Brazilian society will appear in an amplified form if the focus is the incarcerated woman. The State to draw up any appropriate public policy needs reliable data from this area. Bauman calls attention to the growth of the “world of the excluded”. This is more serious when it comes to the gender problem. Gender equality involves very slow modifications and depends on deep transformations that imply changes affecting cultural elements. Many of the women are related to drug trafficking indirectly caught in trying to take their drugged inmate or tied to petty theft related to family survival. The stigma of this woman who came to be arrested is violent because once in prison they are abandoned and forgotten by their respective relatives. Those who are arrested and are pregnant and may come to light while they are serving their feathers run the risk of not seeing their babies again. Engels tells us that gender inequality was the first class antagonism present in the malefemale relationship. The present society is founded on the distributive injustice and loaded of stigmas among which is the one of the woman. Urban violence related to gender affects Brazilian women in general is disproportionate to the poorest who end up involved with drug and crime issues besides domestic violence and street violence.